2021
DOI: 10.1063/5.0035622
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion battery effect via inhomogeneous magnetic anisotropy

Abstract: Magnetic skyrmions are considered as a promising candidate for the next-generation information processing technology. Being topologically robust, magnetic skyrmions are swirling spin textures that can be used in a broad range of applications from memory devices, logic circuits, to neuromorphic computing. In a magnetic medium lacking inversion symmetry, magnetic skyrmion arises as a result of the interplay between magnetic exchange interactions, Dzyaloshinskii-Moriya interaction, and magnetic anisotropy. Instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The total energy as a function of exchange interaction J 1 is plotted in Figure 3B in the presence of an isolated meron (black line) and bimerons (red line). The total energy is dominated by the ferromagnetic region and thus decreased when J 1 is increased [26]. The topological number of merons almost remains the same as shown in Figure 3C, while the diameter of merons decreases with the increasing J 1 as shown in Figure 3D.…”
Section: Numerical Resultsmentioning
confidence: 63%
“…The total energy as a function of exchange interaction J 1 is plotted in Figure 3B in the presence of an isolated meron (black line) and bimerons (red line). The total energy is dominated by the ferromagnetic region and thus decreased when J 1 is increased [26]. The topological number of merons almost remains the same as shown in Figure 3C, while the diameter of merons decreases with the increasing J 1 as shown in Figure 3D.…”
Section: Numerical Resultsmentioning
confidence: 63%
“…From the simulation results and analyses above, one may tailor the skyrmion structure on demand by introducing different energy potential wells or energy potential barriers into the nanostructure via the inhomogeneous PMA distribution. To preserve the rotational symmetry of skyrmion, many studies focused on isolated skyrmions confined in circular nanodisks [8,13], and it was demonstrated that the isolated skyrmions can be stabilized by using inhomogeneous PMA in disk-shaped heterostructure with circle-shaped capping layer [30]. In the simulations, we found that isolated skyrmions can be generated and stabilized in the proposed heterostructures with square-shaped or circle-shaped capping nano-islands.…”
Section: Nucleation Of Skyrmion In Square-shaped Nanostructures With ...mentioning
confidence: 85%
“…In this work, we studied the manipulation of skyrmion mediated by local inhomogeneous PMA in the heterostructures. We proposed an architecture of a capping nano-island fabricated on the top surface of an ultrathin Co/Pt film, in which the PMA strength (K c ) of capping island (Region II) can be largely modified by different capping materials [28][29][30], as schematically shown in Figure 1a. Here, the desired K c can be manufactured by choosing a proper capping material with modified material parameters, e.g., strain and sample thickness.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations